European social policy and social work [ citizenship-based social work - Ewijk, Hans van (Routledge, 2010)
Explores shifts in international social policies and how they affect national trends and thus the context for social work practice. This book discusses international and national social work strategies and practice, and investigates the responsibilities for social welfare held by the state, the market and civil society.